Class 10 Exam  >  Class 10 Questions  >  If x=cosecA+cosA and y=cosecA-cosA then prove... Start Learning for Free
If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0
?
Most Upvoted Answer
If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2...
Answer:

Given : x= cosecA+cosA
y= cosecA-cosA

So, value of x+y= 2 cosecA
and x-y = 2 cosA

Now, {2/(x+y)}²+{(x-y)/2}-1 = (2/2cosecA)²+(2cosA/2)²-1
{2/(x+y)}²+{(x-y)/2}-1 = sin²A+cos²A-1
{2/(x+y)}²+{(x-y)/2}-1 = 1-1
{2/(x+y)}²+{(x-y)/2}-1 = 0
Hence proved.

Hope its help you.
Community Answer
If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2...
Given:
x = cosecA cosA
y = cosecA - cosA

To prove:
(2/x y)^2 (x-y/2)^2 - 1 = 0

Proof:

Step 1: Rewrite the given expressions
x = 1/sinA cosA (since cosecA = 1/sinA)
y = 1/sinA - cosA

Step 2: Simplify the expressions
x = cosA/sinA (multiply numerator and denominator by cosA)
y = (1 - sinA cosA)/sinA (common denominator)

Step 3: Substitute the values of x and y in the given expression
(2/x y)^2 (x - y/2)^2 - 1 = 0

Substituting the values of x and y,
(2/(cosA/sinA)(1 - sinA cosA)/sinA)^2 [(cosA/sinA) - (1 - sinA cosA)/2sinA]^2 - 1 = 0

Step 4: Simplify the expression inside the brackets
[(2sinA)/(cosA(1 - sinA cosA))]^2 [(2cosA - (1 - sinA cosA))/(2sinA)]^2 - 1 = 0

Simplifying further,
[(2sinA)/(cosA - sin^2AcosA)]^2 [(2cosA + sinA cosA - 1)/(2sinA)]^2 - 1 = 0

Step 5: Simplify the expression
[(2sinA)/(cosA - sin^2AcosA)]^2 [(2cosA + sinA cosA - 1)/(2sinA)]^2 - 1 = 0

Since the numerator and denominator of the first term are squared, they cancel each other out,
(2cosA + sinA cosA - 1)^2 - (cosA - sin^2AcosA)^2 = 0

Step 6: Simplify further
Expanding the squares,
(4cos^2A + 4sinA cosA - 2cosA - 2sinA cos^2A - 2sin^2AcosA + 1) - (cos^2A - 2sin^2AcosA + sin^4Acos^2A) = 0

Simplifying the expression,
4cos^2A + 4sinA cosA - 2cosA - 2sinA cos^2A - 2sin^2AcosA + 1 - cos^2A + 2sin^2AcosA - sin^4Acos^2A = 0

Combining like terms,
3cos^2A + 4sinA cosA - cosA + 2sin^2A - sin^4Acos^2A + 1 = 0

Step 7: Rearrange the terms
Rearranging the terms in descending powers of sinA and cosA,
-sin^4Acos^2A + 3cos^2
Explore Courses for Class 10 exam
Question Description
If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? for Class 10 2025 is part of Class 10 preparation. The Question and answers have been prepared according to the Class 10 exam syllabus. Information about If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? covers all topics & solutions for Class 10 2025 Exam. Find important definitions, questions, meanings, examples, exercises and tests below for If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics?.
Solutions for If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? in English & in Hindi are available as part of our courses for Class 10. Download more important topics, notes, lectures and mock test series for Class 10 Exam by signing up for free.
Here you can find the meaning of If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? defined & explained in the simplest way possible. Besides giving the explanation of If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics?, a detailed solution for If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? has been provided alongside types of If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? theory, EduRev gives you an ample number of questions to practice If x=cosecA+cosA and y=cosecA-cosA then prove that (2/x+y)^2+(x-y/2)^2-1=0 Related: Trigonometric Ratios Part 1 - Introduction to Trigonometry, CBSE, Class 10, Mathematics? tests, examples and also practice Class 10 tests.
Explore Courses for Class 10 exam
Signup to solve all Doubts
Signup to see your scores go up within 7 days! Learn & Practice with 1000+ FREE Notes, Videos & Tests.
10M+ students study on EduRev